Effect of seed priming with mixed-salt solution on germination and physiological characteristics of seedling in rice (Oryza sativa L.) under stress conditions - HE Chang-zheng; HU Jin; ZHU Zhi-yu; RUAN Song-lin; SONG Wen-jian (浙江大学学报. 农业与生命科学版, 2002)
The effect of seed priming with mixed-salt solution on germination and physiological characteristics of seedling in rice was investigated by determining percentage germination and germination index, activities of several enzymes under low-temperature (5 ℃) stress and salt stress (O.58% NaCl) conditions. The results showed that germination of the primed seeds was significantly more rapid than the control under two kinds of stress. No significant changes in activities of seed α-amylase and root system dehydrogenase were observed while activities of seed β-amylase and shoot catalase were enhanced under low temperature stress. Significant increase in the activity of seed α-amylase, β-amylase and root system dehydrogenase and moderate rise in the activity of shoot catalase occurred under salt stress.